License Plate Detection of Myanmar Vehicle Images Captured from the Dissimilar Environmental Conditions - Khin, Ohnmar; Phothisonothai, Montri; Choomchuay, Somsak (My University, 2018)
Due to the difficulty in defecting the images, in this paper, we proposed the method that can detect region of interest of the license plate for Myanmar vehicles captured from the dissimilar environmental conditions, e.g., different type of license plates, angle of image capturing, and real environmental conditions. In this paper, the horizontal and vertical dilation, skew angle detec-tion and automatic bounding box were proposed to detect the license number from input images. In our experiment, the ob-tained results showed that an average detection accuracy of 99% which was substantially applied for the license plate detection from the dissimilar environmental conditions.
Keywords: Bounding box; Car license plate recognition (CLPR); Horizontal and vertical dilation; License plate detection; Myanmar license plate; Skew angle detection